The Implementation of Animated Video Media in Improving Arabic Vocabulary Masteryof Students at Madrasah Aliyah Ibadurrahman Stabat Langkat - Atzally Maharani Irtin; Zahrodin Fanani; Joko Ariyanto (PT. Pusmedia Group Indonesia, 2025)
This study aims to examine the implementation of animated video media in improving students’ mastery of Arabic vocabulary at Madrasah Aliyah Ibadurrahman Stabat Langkat. The background of this research stems from the low level of Arabic vocabulary mastery, which affects students’ overall language skills. Conventional teaching methods, which tend to be monotonous and text-based, often result in a lack of motivation and enthusiasm among students. Therefore, animated video media was introduced as an innovative and interactive alternative to enhance the effectiveness of Arabic language learning.This study employed a descriptive qualitative method with data collected through observation and interviews involving teachers and students. The findings indicate that the use of animated video media significantly increases students’ interest and engagement during Arabic lessons. The integration of visual and auditory elements helps students understand vocabulary meanings in a contextual manner, making the learning process more effective. Furthermore, teachers become more creative and adaptive in designing technology-based learning activities suited to students’ characteristics and learning styles.However, the study also found several challenges, including dependence on technological tools such as projectors, laptops, and internet connectivity. These technical constraints may hinder the learning process if not properly managed. Overall, the use of animated video media has proven to be an effective strategy for improving Arabic vocabulary mastery and fostering students’ motivation to actively participate in language learning activities.